Inhibition of FLT3-ITD Kinase in Acute Myeloid Leukemia by New Imidazo[1,2-b]pyridazine Derivatives Identified by Scaffold Hopping - Břehová, Petra; Řezníčková, Eva; Škach, Kryštof; Jorda, Radek; Dejmek, Milan; Vojáčková, Veronika; Šála, Michal; Kovalová, Markéta; Dračínský, Martin; Dolníková, Alexandra; Strmeň, Timotej; Kinnertová, Monika; et al. (Journal of medicinal chemistry, 2023)
FLT3 kinase is a potential drug target in acute myeloid leukemia (AML). Patients with FLT3 mutations typically have higher relapse rates and worse outcomes than patients without FLT3 mutations. In this study, we investigated the suitability of various heterocycles as central cores of FLT3 inhibitors, including thieno[3,2-d]pyrimidine, pyrazolo[1,5-a]pyrimidine, imidazo[4,5-b]pyridine, pyrido[4,3-d]pyrimidine, and imidazo[1,2-b]pyridazine. Our assays revealed a series of imidazo[1,2-b]pyridazines with high potency against FLT3. Compound 34f showed nanomolar inhibitory activity against recombinant FLT3-ITD and FLT3-D835Y (IC50 values 4 and 1 nM, respectively) as well as in the FLT3-ITD-positive AML cell lines MV4-11, MOLM-13, and MOLM-13 expressing the FLT3-ITD-D835Y mutant (GI50 values of 7, 9, and 4 nM, respectively). In contrast, FLT3-independent cell lines were much less sensitive. In vitro experiments confirmed suppression of FLT3 downstream signaling pathways. Finally, the treatment of MV4-11 xenograft-bearing mice with 34f at doses of 5 and 10 mg/kg markedly blocked tumor growth without any adverse effects.
Keywords: Leukemia, Myeloid, Acute; tyrosinkinasa 3 podobná fms; Humans; inhibitory proteinkinas; pyrimidiny; mutace; Antineoplastic Agents; Pyridazines; pyridaziny; lidé; zvířata; myši; Mice; apoptóza; Protein Kinase Inhibitors; nádorové buněčné linie; protinádorové látky; fms-Like Tyrosine Kinase 3; Animals; Cell Line, Tumor; Mutation; Pyrimidines; akutní myeloidní leukemie; Apoptosis